1995
DOI: 10.1111/j.1439-0507.1995.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural investigation of Malassezia furfur. II. The envelope of the yeast cells

Abstract: The general ultrastructure of the Malassezia furfur cell envelope is shown in a schematic model. Distinct layers such as the outer lamella, the cell wall and the plasma membrane and special structural elements of the cell wall are described and presented in electronmicrographs. Special attention was paid to the outer lamellar layer that seems to be equivalent to a capsule. It probably contains lipids as well as the cell wall, and it seems to participate in attachment processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 36 publications
1
56
2
1
Order By: Relevance
“…It has been shown that this lipid dependency is due to a defect in the synthesis of myristic acid, which serves as the precursor of long-chain fatty acids (Porro et al, 1976;Shifrine & Marr, 1963). Even so, the outermost layer of the complex cell wall consists mainly of lipids (Mittag, 1995), which are thought to be involved in the pathogenesis of this fungus. Similar to the polysaccharide capsule of Cryptococcus neoformans (Ellerbroek et al, 2004), this lipid layer seems to protect M. furfur from phagocytosis (Ashbee & Evans, 2002) and downregulates the inflammatory immune response (Kesavan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this lipid dependency is due to a defect in the synthesis of myristic acid, which serves as the precursor of long-chain fatty acids (Porro et al, 1976;Shifrine & Marr, 1963). Even so, the outermost layer of the complex cell wall consists mainly of lipids (Mittag, 1995), which are thought to be involved in the pathogenesis of this fungus. Similar to the polysaccharide capsule of Cryptococcus neoformans (Ellerbroek et al, 2004), this lipid layer seems to protect M. furfur from phagocytosis (Ashbee & Evans, 2002) and downregulates the inflammatory immune response (Kesavan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There is an inconsistently visible intermediate zone that separates the main layers. The main layers may be further lamellated, thus revealing a multi-layered substructure 3 . The Malassezia yeast cell wall is composed of an unusually high lipid content (15∼ 20%).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the genus Malassezia has lipid-rich multiple layers on the cell wall [3][4][5] . It is thought that the lipid-rich layers play a critical role in physiologic and pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The protoplasmic membrane is firmly attached to the inside of the cell wall. The major components of the cell wall are mannoproteins (75 to 80%), lipids (15 to 20%), and chitin (1 to 2%) (105). It is thought that the immunomodulatory capacity of the Malassezia yeasts are related to cell wall lipids.…”
Section: Malasseziamentioning
confidence: 99%